Microbial dysbiosis and the aging process: a review on the potential age-deceleration role of Lactiplantibacillus plantarum - Gupta, Nishant; El-Gawaad, N. S. Abd; Mallasiy, L. O.; Gupta, Harsh; Yadav, Virendra Kumar; Alghamdi, Saad; Qusty, Naeem F. (Frontiers in Microbiology, 2024)
Gut microbiota dysbiosis has been a serious risk factor for several gastric and systemic diseases. Recently, gut microbiota’s role in aging was discussed. Available preclinical evidence suggests that the probiotic bacteria Lactiplantibacillus plantarums (LP) may influence the aging process via modulation of the gut microbiota. The present review summarized compelling evidence of LP’s potential effect on aging hallmarks such as oxidative stress, inflammation, DNA methylation, and mitochondrial dysfunction. LP gavage modulates gut microbiota and improves overall endurance in aging animal models. LP cell constituents exert considerable antioxidant potential which may reduce ROS levels directly. In addition, restored gut microbiota facilitate a healthy intestinal milieu and accelerate multi-channel communication via signaling factors such as SCFA and GABA. Signaling factors further activate specific transcription factor Nrf2 in order to reduce oxidative damage. Nrf2 regulates cellular defense systems involving anti-inflammatory cytokines, MMPs, and protective enzymes against MAPKs. We concluded that LP supplementation may be an effective approach to managing aging and associated health risks.